Cytocompatibility of nitrogen plasma ion immersed medical cobalt–chromium alloys. Issue 6 (26th June 2013) - Schröck, Kathleen; Schneider, Heike; Lutz, Johanna; Hacker, Michael C.; Mändl, Stephan; Kamprad, Manja; Schulz‐Siegmund, Michaela
Abstract Wear particles and ion release from medical CoCr contribute to the risk for aseptic loosening. Nitrogen plasma immersion ion implantation (PIII) has been shown to reduce wear of CoCr but is associated with increased Co ion release. This work investigated the cytocompatibility of CoCr modified by nitrogen PIII at different temperatures (mCoCr). The osteosarcoma cell line Saos‐2, mesenchymal stem cells (MSCs), and mononuclear cells (MNCs) were grown directly on CoCr/mCoCr discs or treated with CoCl2. Proliferation and metabolic activity of Saos‐2 and MSC were decreased on mCoCr in correlation with increasing implantation temperature. The elevated Co ion release seemed to play a decisive role since analog effects were observed by treatment of cells with CoCl2. Proliferation of phytohemagglutinin‐stimulated MNC was reduced in the presence of CoCr discs or CoCl2. For MNC‐alloy cultures we observed an increase in interleukin 2 (IL‐2) and a decrease in interferon γ (IFN‐γ) and IL‐10 secretion compared to cultures without alloys. The results of this study demonstrate that PIII process temperature and corresponding Co ion release correlate with material cytocompatibility. Therefore, the two competing parameters, reduction of wear and increase in Co ions, have to be taken into consideration for the evaluation of the clinical applicability of nitrogen‐implanted CoCr. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1744–1754, 2014.